Students' use of the young adult collection at the Immaculate Conception Cathedral School High School Library - Sta. Ana, Ann Marie C. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
One of the most important duties of a school library and media center is to make resources and services accessible and available to its users. Aside from its main function which is to support the curriculum of the school, it has many other secondary functions such as stimulating the imagination of children, promoting critical thinking, exposing children to diverse points of view, and providing entertaining diversions (Rubin, 2000). These functions are fulfilled by the library by promoting and encouraging students to read; more specifically recreational or voluntary reading.